Effects of simulated acid rain on in vitro pollen performance of pyrus communis L. and Malus Sylvestris Miller - Topdemir, Aykut; Gür, Nazmi (My University, 2012)
Successful fruit set depends on several reproductive processes including pollen germination and lube growth processes. Pollens of/V/'W connnniiis L. and Mains sy/veslris Millet flowers have been exposed lo different concentrations of simulated acid rain solutions in range of pHs 6.0 to 2.8. Brawbakcr Kwack medium was used for pollen germination. According to the results obtained, germination rate and pollen tube length for each plant at least has been affected at pi I 6.0. Pollen germination and tube length significantly decreased with increasing acidity. The decrease of these rales for Mains sytvestris Miller was 99.44% for pollen germination and 99.68% lor lube length: and for Pyrus communis I... 96.23% for pollen germination and 96.75% for tube length at a pH of 2.8. It has been shown that acidity has a higher effect on blocking Ma/us sylveslrii Miller pollen performance in vitro comparative with Pyrus communis L.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Acid rain; Apple; Pear; Pollen; Germination; Tube growth